Novosti v študiju geodezije - Vodopivec, Florjan (Geodetski vestnik, 1994)
A short review of the up to the present surveying university study in Ljubljana, Slovenia, is presented. Directives and starting-points for the university and high proffesional study of surveying are described
Keywords: geodesy; geodezija; surveying university study; študij geodezije